Immigrant Children's Perception of the Film "Mother's Power": Thematic Analysis and Activity Based Costing (ABC) Methods on Learning Motivation and Psychological Factors in Malaysia - Marfu'ah, Hesti (Sultan Journal of Social Sciences and Humanities, 2025)
This study aims to describe immigrant children’s perceptions of the film “Kekuatan Ibu” and to analyze its influence on learning motivation and psychological factors at Sanggar Bimbingan Sungai Mulia 5 (SBSM5), Gombak, Malaysia. The research employed a qualitative descriptive approach with open-ended questionnaires distributed to twenty-five children aged 11 to 13 who had watched the film. Data were analyzed using thematic analysis combined with the Activity Based Costing (ABC) method to identify key elements shaping children’s learning experiences. The findings reveal that psychological aspects emerged as the most significant, as children often expressed feelings of sadness, loneliness, and emotional struggle when learning without direct parental support. Personal aspects were reflected in their sense of responsibility, self-motivation, and strategies for independent study, while social aspects were linked to the limited assistance provided by family members or peers. Overall, the film served as a reflective medium that transformed children’s emotional challenges into renewed motivation to learn and a deeper appreciation for their mothers’ sacrifices. The group viewing activity also fostered stronger academic engagement and a sense of togetherness. The study concludes that media-based educational interventions hold considerable potential in enhancing learning motivation, resilience, and emotional well-being among immigrant children in community-based learning settings.